BILINGUALISM IN THE DIGITAL ERA: UTILIZING LANGUAGES IN ONLINE COMMUNITIES AND EXAMINING ITS INFLUENCE ON CULTURAL IDENTITY - Aneeza; Dr. Aqsa Atta (International Journal of Contemporary Issues in Social Sciences, 2023)
The intricate interplay between language and identity forms a compelling focus within bilingual communities, introducing complexity to the individual sense of self. Employing a mixed-method approach, this current research delves into the exploration of language utilization and its consequential impact on the perceptual landscape of cultural identity within bilingual cohorts. The investigation extends its purview to scrutinize the strategic negotiation of identity by individuals across various social media platforms. Additionally, the study delves into the ramifications of bilingualism on interactional practices. Data, emanating from the Shireen Gheba’s online community, coupled with interviews featuring influential bilingual bloggers, underwent meticulous analysis utilizing the content analysis technique. The study’s discernments reveal that a purposeful amalgamation of languages is strategically employed to foster relationships, surmount cultural barriers, and resonate with a diverse audience. Furthermore, this linguistic amalgamation serves to challenge conventional norms, reshape linguistic paradigms, and advocate for linguistic diversity within the digital sphere. This research proffers profound insights into the evolving dynamics of digital discourse, presenting implications of considerable import for the burgeoning domain of bilingual digital communities.p>